59.1k views
2 votes
2b-9=5b+6Must include check

1 Answer

3 votes

According to the given data we have the following equation:

2b-9=5b+6

To solve the variable b of the equation we would make the following:

2b-9=5b+6

First move the variable 5b to the left side, and -9 to the right side.

So:

2b-5b=6+9

Next, add all the elements

-3b=15

Finally calculate b by dividing 15/-3

b=15/-3

b=-5

Therefore, if the variable b=-5, hence check:

2b-9=5b+6

2(-5)-9=5(-5)+6

-10-9=-25+6

-19=-19

User Yan Zhu
by
4.7k points